Towards Sustainable Mobility? Challenges of the public transportation reorganization policies in Latin America. The case of Lima - Poole-Fuller, Esteban (2017)
During the last two decades, several Latin American cities have reorganized their public transportation services, which displayed low quality standards, into integrated transit systems with increased levels of State planning and regulation. This trend has come along with an increasing support to the sustainable mobility approach, which seeks to overcome urban policies which had been focused on individual cars, promoting means of displacement which are socially and environmentally more sustainable. Taking into account such context, this paper will analyze the experience of reorganization of public transportation in the city of Lima. It will also compare it to previous processes of reorganization of urban mobility in Curitiba, Santiago de Chile and Bogota. The paper concludes that the process of reorganization of Lima’s public transport, currently unfinished, requires a series of adjustments in its design and implementation in order to assure that it effectively enhances the establishment of a sustainable mobility model in the Peruvian capital.